Content Marketing Strategy in Increasing Student MSME Brand Awareness - Pius Deski Manalu; Dedi Irawan; Mutiara S. Simanjuntak; Dody Hidayat (STMIK Methodist Binjai, 2026)
This study is motivated by the low level of brand awareness among student-owned micro, small, and medium enterprises (MSMEs), which is mainly caused by the suboptimal implementation of digital marketing strategies, particularly content marketing. The main problem addressed in this research is how content marketing strategies can improve brand awareness among student MSMEs. This study aims to analyze the effect of content marketing on brand awareness and to identify effective content strategies that support such improvement. The research employs a quantitative approach using a survey method involving 100 student MSME actors in the Padang Bulan area. Data were collected through questionnaires using a Likert scale and analyzed using simple linear regression and t-test. The results indicate that content marketing has a positive and significant effect on brand awareness, with a regression coefficient of 0.68 and a significance value of 0.000 (less than 0.05). Additionally, about 78% of respondents actively use social media for marketing purposes, while only 65% ​​have structured content strategies. This finding suggests that improving content quality, creativity, and consistency can significantly enhance brand awareness. This study is expected to provide practical insights for student MSMEs in optimizing content-based digital marketing strategies.